The Conservatism of Emoji: Affect and Labor in Informational Capitalism - Stark, Luke; Crawford, Kate (Social Media + Society, 2015)
This piece examines emoji as conduits for affective labor in the social networks of informational capitalism. Emoji, ubiquitous digital images that can appear in text messages, emails, and social media chat platforms, are rich in social, cultural, and economic significance. This article examines emoji as historical, social, and cultural objects, and as examples of skeuomorphism and of technical standardization. Now superseded as explicitly monetized objects by other graphics designed for affective interactions, emoji nonetheless represent emotional data of enormous interest to businesses in the digital economy, and continue to act symbolically as signifiers of affective meaning. We argue that emoji characters both embody and represent the tension between affect as human potential, and as a productive force that capital continually seeks to harness through the management of everyday biopolitics. Emoji are instances of a contest between the creative power of affective labor and its limits within a digital realm in the thrall of market logic.